Estudo conformacional do ritonavir no vácuo e em meio aquoso usando dinâmica molecular de Car-Parrinello - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Ritonavir is an oral antiretroviral, used together with other medicines to treat HIV / AIDS. Doses of this drug are used simultaneously with others protease inhibitors and there are also reports of the use of ritonavir with other drugs to prevent hepatitis C. They were reported different polymorphic forms of ritonavir two years after the beginning of the market, when the capsules started to show dissolution problems consequently to the lower bioavailability. X-ray analysis showed the formation of a less soluble polymorph. Phenomena related to solubility and bioavailability of drugs are closely linked to the chemical structure of the same and with the interaction of molecules with solvents, therefore, the main objective of this study is to evaluate the effects of aqueous solvation on the geometric and electronic parameters of ritonavir using as tool Molecular dynamics of Car-Parrinello. The cores of the electrons were treated through the pseudopotential ultrasoft Vanderbilt, and the valence electrons were represented by the set of plane waves basis functions. The power cut (Ecut) was adopted 25 Ry and cutting power to the charge density (Ecutrho) was adopted 200 Ry. The temperatures of the studied systems were controlled using NoséHoover thermostat at 300 K. The simulation results show that hydration induces to formation of several hydrogen bridges between ritonavir hydrophilic groups and water molecules, there were also protonation of two nitrogens present in the drug. The adiabatic separation remained constant during the simulation, ensuring that there was no exchange of energy between the ionic and electronic system.
Keywords: Ritonavir; Dinâmica Molecular; Car-Parrinello; Hidratação; Ritonavir; Molecular dynamics; Car-Parrinello; Hydration; CIENCIAS EXATAS E DA TERRA::QUIMICA